2022
DOI: 10.1038/s41598-022-22534-0
|View full text |Cite
|
Sign up to set email alerts
|

Women’s quality of sleep and in vitro fertilization success

Abstract: Women undergoing in vitro fertilization (IVF) are emotionally challenged. Anxiety, depression, and sleep disturbances are common complaints. The impact of these symptoms on IVF outcome is however debated. In this study, we aimed at investigating whether sleep quality and psychological health can affect the chances of success of the procedure. Women undergoing IVF were recruited at the time of oocytes retrieval. Women’s sleep quality and psychological health was assessed using the Pittsburgh Sleep Quality Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Approximately 10% of the participants reported sleep latency longer than 30 minutes, 8.2% reported sleep duration less than 7 hours, and 23.9% reported less than 85% sleep efficiency. The incidence of poor sleep in this study was similar to the results of Yang’s ( 53 ) and Reschini’s ( 52 ) studies. Sleep quality may fluctuate with treatment cycles and measurement criteria.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Approximately 10% of the participants reported sleep latency longer than 30 minutes, 8.2% reported sleep duration less than 7 hours, and 23.9% reported less than 85% sleep efficiency. The incidence of poor sleep in this study was similar to the results of Yang’s ( 53 ) and Reschini’s ( 52 ) studies. Sleep quality may fluctuate with treatment cycles and measurement criteria.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also found that women with sleep efficiency < 85% had a reduced clinical pregnancy rate compared with women with sleep efficiency ≥ 85%, supporting previous studies. Previous studies reported that long or short nocturnal sleep was associated with a reduced clinical pregnancy rate ( 32 , 52 , 77 , 78 ). Liu et al.…”
Section: Discussionmentioning
confidence: 97%
“…The quality and duration of sleep have been reported to affect infertility treatment outcomes ( 48 ), and Goldstein et al. reported that there tended to be a correlation between sleep duration and the number of oocytes retrieved in IVF treatment ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that evening use of light-emitting eReaders negatively affects sleep ( 50 ) and that the quality and duration of sleep affect IVF outcomes ( 16 , 48 ). There are no reports about the relationship between use of computers and light-emitting eReaders and IVF outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they revealed a signi cant positive relationship between sleep quality and symptoms of depression and anxiety, suggesting a possible correlation between sleep quality and pregnancy outcomes(30). Similarly,Reschini et al (2022) demonstrated that poor sleep quality was prevalent in women experiencing IVF, affecting the success of this procedure(15). In addition, Liu et al(2022) concluded that sleep quality and timing before ET were associated with the IVF outcomes, and good sleep quality was an effective factor for pregnancy, such as conception and live birth(31).Likewise, Mengye et al (2022) established that poor sleep quality in the rst and second trimesters could negatively in uence the weight of the IVF baby girls and underlined that early screening and interventions focused on sleep quality improvement could reduce the adverse consequences of poor sleep.…”
mentioning
confidence: 95%